Effects of Vestibular Rehabilitation on Physical Activity and Subjective Dizziness in Patients With Chronic Peripheral Vestibular Disorders: A Six-Month Randomized Trial - Shiozaki, Tomoyuki; Ito, Taeko; Wada, Yoshiro; Yamanaka, Toshiaki; Kitahara, Tadashi (Frontiers in Neurology, 2021)
Introduction: The present study aimed to determine whether supervised vestibular rehabilitation therapy (VRT) by physical therapists (PTs) affects subjective dizziness in patients with chronic vestibular disorders, and whether supervised VRT-induced changes in subjective dizziness are related to the changes in physical activity levels in daily life. Methods: Patients (n = 47) with chronic peripheral vestibular disorders were randomly divided into the VRT group (n = 25) and control group (n = 22). Patients in the VRT group received weekly supervised visits from PTs for a period of 6 months. Every other month, both groups were advised by neuro-otologists to increase the amount of activity in their daily life. All patients wore an accelerometer device, which recorded their physical activity for seven successive days before the end of the intervention. Patients also completed the dizziness and unsteadiness questionnaires before and after the intervention. Results: Subjective dizziness decreased significantly regardless of whether supervised VRT was administered; however, dizziness evoked by social activity and head and body movements improved more significantly in the VRT group than in the control group. In the VRT group, there was a significant negative correlation between the increase in sedentary behavior and improvement in subjective dizziness, and a significant positive correlation between the increase in light physical activity and improvement in subjective dizziness at the second month of intervention. The VRT group showed a significantly higher rate of increase in light physical activity than the control group, after 6 months of intervention. Conclusion: Supervised VRT could be highly effective in treating subjective dizziness in patients with chronic peripheral vestibular disorders. We believe frequent (weekly) and medium-term (6 months) PT-guided interventions may be highly effective in enhancing physical activity in daily life, and may subsequently improve subjective dizziness in these patients. Trial registration: This clinical study was registered with University hospital Medical Information Network (identification number: 000028832). https://www.umin.ac.jp/